A rare condition that may be confused with testicular torsion in children-testicular band - Hanbeyoglu, A.; Tartar, T.; Bakal, U.; Akkus, T.; Kazez, A. (Medpharm Publications Pty Ltd, 2025)
Testicular torsion (TT) is the most important cause of acute scrotum in children, which can lead to testicular loss and requires emergency surgery. Fibrotic bands around the epididymis/spermatic cord that can cause severe testicular ischemia are extremely rare. The origin of these bands is unknown. Although scrotal colour doppler ultrasonography (CDUS) has an important place in the diagnosis of TT, it may be insufficient in the diagnosis of the bands. We aimed to present two rare cases in which a band was detected surrounding the distal spermatic cord and causing testicular ischemia in patients who had no previous scrotal pathology and emergency surgery was performed considering TT.
Keywords: child; testicular torsion; testicular band; acute scrotum; testicular surgery